2022
DOI: 10.1177/11206721221113202
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel wall imaging using fluorescein angiography and adaptive optics imaging in acute branch retinal artery occlusion

Abstract: Purpose To report the retinal vessel wall changes in a patient with acute branch retinal artery occlusion with fundus fluorescein angiography and adaptive optics imaging. Methods Retrospective, observational case Case description A 49-year-old female with cardiac ailment complained of sudden onset superior field loss for 4 days in her right eye. Her presenting visual acuity in the right eye was 20/20, N6. She was diagnosed with right eye infero-temporal branch retinal artery occlusion. A golden-yellow, round c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Multimodal imaging using FA, Fundus autofluorescence, OCT, OCTA, and adaptive optics was used to image a case of branch retinal artery occlusion (BRAO) in which the causative embolus was present at the inferior bifurcation of the nasal and temporal branches of the central retinal artery. 46 …”
Section: Current Research and Techniques In The Study Of Ischemic Pen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodal imaging using FA, Fundus autofluorescence, OCT, OCTA, and adaptive optics was used to image a case of branch retinal artery occlusion (BRAO) in which the causative embolus was present at the inferior bifurcation of the nasal and temporal branches of the central retinal artery. 46 …”
Section: Current Research and Techniques In The Study Of Ischemic Pen...mentioning
confidence: 99%
“…Multimodal imaging using FA, Fundus autofluorescence, OCT, OCTA, and adaptive optics was used to image a case of branch retinal artery occlusion (BRAO) in which the causative embolus was present at the inferior bifurcation of the nasal and temporal branches of the central retinal artery. 46 The ischemic penumbra that occurs following partial CRAO has two components a homogenous annular penumbra in the mid-periphery and a heterogenous macular penumbra. It has been suggested that this enduring ischemic penumbral tissue can be identified using hypoxia tracers such as fluoromisonidazole.…”
Section: Current Research and Techniques In The Study Of Ischemic Pen...mentioning
confidence: 99%